2005
DOI: 10.1080/10425170500061665
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression studies of the Dunaliella salina UDP-glucose dehydrogenase cDNA

Abstract: The enzyme UDP-glucose dehydrogenase (EC 1.1.1.22) converts UDP-glucose to UDP-glucuronate. Plant UDP-glucose dehydrogenase (UGDH) is an important enzyme in the formation of hemicellulose and pectin, the components of primary cell walls. A cDNA, named DsUGDH, (GeneBank accession number: AY795899) corresponding to UGDH was cloned by RT-PCR approach from Dunaliella salina. The cDNA is 1941-bp long and has an open reading frame encoded a protein of 483 amino acids with a calculated molecular weight of 53 kDa. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In plants, the gene encoding UGD activity was first described in soybean (76,148). Subsequently, numerous UDP-GlcDH genes encoding proteins with high amino acid sequence similarity to one another were identified in Arabidopsis, poplar (68), tobacco (15), maize (72), and Dunaliella (122). Each plant has multiple UGD isoforms and their specific activities are of interest because studies with sugar cane revealed that CTP-glucose and TDPglucose were also oxidized, albeit less effectively than UDP-Glc (154).…”
Section: Udp-α-d-glucuronic Acidmentioning
confidence: 99%
“…In plants, the gene encoding UGD activity was first described in soybean (76,148). Subsequently, numerous UDP-GlcDH genes encoding proteins with high amino acid sequence similarity to one another were identified in Arabidopsis, poplar (68), tobacco (15), maize (72), and Dunaliella (122). Each plant has multiple UGD isoforms and their specific activities are of interest because studies with sugar cane revealed that CTP-glucose and TDPglucose were also oxidized, albeit less effectively than UDP-Glc (154).…”
Section: Udp-α-d-glucuronic Acidmentioning
confidence: 99%
“…The enzyme is well characterized from numerous organisms and crystal structures are available. In plants, the gene encoding this activity was first described in soybean (460), and soon after, as genome sequence became available, numerous UDPGDH gene isoforms that share high amino acid sequence similarity to each other were identified in Arabidopsis (461), poplar (462), tobacco (463), maize (464), and Dunaliella (465). In Arabidopsis, four UDPGDH isozymes are present and, likewise, multiple UDPGDH isoforms are found in the genome of every plant species that has been sequenced.…”
Section: Udp-glc Dehydrogenase (Ugd)mentioning
confidence: 99%